Acupuncture for heart failure: A systematic review of clinical studies. (1st November 2016) - Lee, Hojung; Kim, Tae-Hun; Leem, Jungtae
Abstract: Background: Acupuncture has been used for treating heart failure mainly in combination with conventional treatments, but evidence for its effectiveness and safety has not been well established. Our aim was to review randomized controlled trials (RCTs) on acupuncture for heart failure and assess the clinical evidence. Methods: Electronic databases such as Medline, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL) and certain Chinese & Korean databases were searched until October 2015. The main outcomes assessed were mortality, New York Heart Association (NYHA) function classifications, and acupuncture-related adverse events. The details of acupuncture intervention were also investigated. Results: Among 4107 publications, seven RCTs were included; most of them showed considerable methodological flaws. We could not conduct a meta-analysis because of the heterogeneity of the included studies. In one acute heart failure study, acupuncture shortened intensive care unit (ICU) stay by 2.2 days (95% CI 1.26, 3.14) and reduced the risk ratio of re-admission to 0.53 (95% CI 0.28, 0.99). However, mortality was not affected. Hemodynamic parameters also showed improvement. Another study reported an improved left ventricular ejection fraction by 9.95% (95% CI 3.24, 16.66). In five chronic heart failure studies, acupuncture improved exercise capacity, quality of life, hemodynamic parameters, and time domain heart rate variability parameters. Acupuncture decreased NT-pro BNP levels by 292.20 (95% CI − 567.36, − 17.04). No adverse effects were reported. Conclusions: The effectiveness of acupuncture as a therapy for heart failure is currently inconclusive. Further large and rigorous clinical trials are needed to establish its clinical utility.